Advances in Physical Agents Proceedings of the 19th International Workshop of Physical Agents (WAF 2018), November 22-23, 2018, Madrid, Spain - Fuentetaja Pizán, Raquel; García Olaya, Ángel; Sesmero Lorente, Maria Paz; Iglesias Martínez, Jose Antonio; Ledezma Espino, Agapito (Advances in Intelligent Systems and Computing, 2019)
The book reports on cutting-edge theories and methods aimed at the control and coordination of agents acting and moving in a dynamic environment. It covers a wide range of systems, including multiagent systems, domotic agents, robotic manipulators, soccer robots, autonomous and semiautonomous robots, as well as systems for industrial applications. Advances in software agents, sensors, computer visions and other related areas are also thoroughly discussed and presented in detail. Based on the 19th edition of the International Workshop of Physical Agents (WAF 2018), held on November 22-23, 2018, in Madrid, Spain, this book offers a snapshot of the state-of-the-art in the field of physical agents, with a special emphasis on autonomous systems such as mobile robots, industrial process or other complex systems. .